Environmental and economic life cycle assessment of a lightweight solution for an automotive component: A comparison between talc-filled and hollow glass microspheres-reinforced polymer composites. (15th December 2016) - Delogu, M.; Zanchi, L.; Maltese, S.; Bonoli, A.; Pierini, M.
Abstract: Overall, light weighting strategies are mainly analysed in the aim of reducing impact during the use phase of a vehicle. In this paper environmental and economic assessments are combined to evaluate the sustainability of adopting an innovative lightweight material for an automotive component. The analysis is carried out according to the Life Cycle Assessment and Life Cycle Costing methods. A standard solution, based on talc filler-reinforced composite, and an innovative one made with hollow glass micro-spheres as plastic reinforcement, are compared to be applied to a vehicle dashboard. The use of hollow glass micro-spheres has expanded during the last years in the automotive sector, however evaluations of their environmental and economic performances along its whole life cycle have not yet been discussed extensively. In this study particular attention is given to the following aspects: i) balance between the use phase benefit and material production phase; ii) End-of-Life scenarios; iii) analysis of additional indicators besides CO2 emissions; iv) data accuracy concerning manufacturing phase. Results show that hollow glass microspheres-reinforced composite is likely better from an environmental point of view for those impact categories where the use phase is more involved. The increase of material processing impact does not compromise benefits in terms of GWP and PED due to weight reduction, nevertheless it affects resource depletion and ecotoxicity indicators negatively. Overall the End-of-Life phase is not affected significantly. Moreover, despite a higher material cost, the innovative solution was found economically convenient as demonstrated also by the breakeven point (within the life distance). Highlights: Environmental and economic life cycle assessments of an innovative automotive dashboard in lightweighting perspective. Detailed data collection mostly based on primary data directly measured during the industrial process was done. Talc filler-polypropylene reinforced and hollow glass micro-spheres polypropylene composite were compared. Different End-of-Life scenarios were analysed.